Understanding the effect of locked nucleic acid and 2 `-O-methyl modification on the hybridization thermodynamics of a miRNA-mRNA pair in the presence and absence of AfPiwi protein - Kumar, Santosh; Mapa, Koyeli; Maiti, Souvik (Biochemistry, 2014)
miRNAs are some of the key epigenetic regulators of gene expression. They act through hybridization with their target mRNA and modulate the level of respective proteins via different mechanisms. Various cancer conditions are known to be associated with up- and downregulation of the oncogenic and tumor suppressor miRNAs, respectively. The levels of aberrantly expressed oncogenic miRNAs can be downregulated in different ways. Similarly, restoration of tumor suppressor miRNAs to their normal levels can be achieved using miRNA mimics. However, the use of miRNA mimics is limited by their reduced biostability and function. We have studied the hybridization thermodynamics of the miRNA 26a (11-mer, including the seed sequence) guide strand with the mRNA (11-mer) target strand in the absence and presence of AfPiwi protein. We have also inserted locked nucleic acids (LNAs) and 2'-O-methyl-modified nucleotides into the guide strand, in a walk-through manner, to assess their effect on the binding efficiency between guide and target RNA. Insertion of LNA and 2'-O-methyl-modified nucleotides into the guide strand helped to strengthen the binding affinity irrespective of the position of insertion. However, in the presence of AfPiwi protein, these modifications reduced the binding affinity to different extents depending on the position of insertion. Insertion of a modification leads to an increase in the enthalpic contribution with an increased unfavorable entropic contribution, which negatively compensates for the higher favorable enthalpy.